Research in organizational change and development. Volume 18 - Pasmore, William A.; Woodman, Richard W.; Shani, Abraham B. (Research in organizational change and development, 2010)
Volume Eighteen of Research in Organizational Change and Development contains nine papers that address cutting edge challenges in organizational change, report the results of change-related research, and advocate methodological advances in the field. Papers by noted international authors such as Ed Lawler & Chris Worley, Hillary Bradbury, Benyamin Lichtenstein, John Carrol & Peter Senge, Rob Sloyan & Jim Ludema, and David Coghlan make for fascinating reading and set an ambitious agenda for future scholarship.